The Paideia Proposal : an educational manifesto - Adler, Mortimer Jerome, 1902-2001.; Paideia Group (New York : Macmillan Publishing Company, 1982)
A K-12 educational reform plan developed as the result of a two year study by the Paideia Group.
pt. 1: The schooling of a people. Democracy and education -- Schooling-only a part of education -- pt. 2: The essentials of basic schooling. The same objectives for all -- The same course of study for all -- Overcoming initial impediments -- Individual differences -- pt. 3: Teaching and learning. The heart of the matter -- The preparation of teachers -- The principal -- pt. 4: Beyond basic schooling. Higher learning -- Earning a living and living well -- The future of our free institutions.
First vol. of the author's trilogy; the 2nd of which is Paideia problems and possibilities, and the 3rd of which is The Paideia program.
Keywords: Education -- Aims and objectives -- United States; Educational equalization -- United States; Education -- Philosophy